Immunity proteins of dual nuclease T6SS effectors function as transcriptional repressors. (31st May 2021) - Yadav, Sunil Kumar; Magotra, Ankita; Ghosh, Srayan; Krishnan, Aiswarya; Pradhan, Amrita; Kumar, Rahul; Das, Joyati; Sharma, Mamta; Jha, Gopaljee
Abstract :